2019
DOI: 10.1186/s43014-019-0006-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of Agaricus bisporus mushroom in beef burgers: antioxidant, flavor enhancer and fat replacing potential

Abstract: This study aimed to evaluate the potential use of Agaricus bisporus mushroom as a natural antioxidant, fat/salt substitute and flavor enhancer in beef burger. Ten treatments were considered using a fractional factorial design (salt [0.5, 1.25 and 2.0%], fat [10, 15 and 20%] and mushroom content [0, 15 and 30%]). Treatments were characterized by instrumental and sensory measurements. The statistical design indicated that fat content had little influence on the results. The principal component analysis showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…One of the advantages of using mushrooms in meat products is that they already have quite meat-like textures themselves because they have a very firm texture, and their dietary fibre fractions form a dense meaty texture when processed with muscle foods. As a result, they can often be incorporated up to a certain percentage into muscle foods without causing major adverse effects on their textural attributes [ 53 , 127 ]. Changes in quality aspects especially textural attributes of muscle foods due to incorporation of mushroom can be assessed from different studies is listed in Table 2 .…”
Section: Effect Of Mushrooms On Quality Aspects Of Muscle Food Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the advantages of using mushrooms in meat products is that they already have quite meat-like textures themselves because they have a very firm texture, and their dietary fibre fractions form a dense meaty texture when processed with muscle foods. As a result, they can often be incorporated up to a certain percentage into muscle foods without causing major adverse effects on their textural attributes [ 53 , 127 ]. Changes in quality aspects especially textural attributes of muscle foods due to incorporation of mushroom can be assessed from different studies is listed in Table 2 .…”
Section: Effect Of Mushrooms On Quality Aspects Of Muscle Food Productsmentioning
confidence: 99%
“…Incorporation of white winter mushroom powder into emulsion-type pork sausages was reported to have little impact on their appearance [ 109 ]. Similarly, incorporation of up to 20% A. bisporus mushroom into beef burgers did not strongly affect their appearance [ 127 ]. The introduction of shiitake mushroom powder into frankfurters had little impact on their initial colour but did increase their yellowness during storage [ 169 ].…”
Section: Effect Of Mushrooms On Quality Aspects Of Muscle Food Productsmentioning
confidence: 99%
“…According to the authors, the high water and moisture retention of mushrooms helps to reduce the cooking losses by water lost [17]. In a previous work of the same authors [49], the reduction of fat was combined with salt reduction up to 75% and similar results were obtained. Ceron-Guevara et al [45] used Agaricus bisporus as well as Pleurotus ostreatus (2.5% and 5%) to replace 50% of animal fat in beef burgers.…”
Section: Fat Replacermentioning
confidence: 62%
“…A study conducted on the digested protein from the common mushroom showed that it possessed natural functional properties in suppressing oxidative stress and suggested its potential application in the food industry as alternative natural antioxidants [ 67 ]. This white mushroom has been extensively studied and many reports have examined and discussed its antioxidant ability from both wild and cultivated Agaricus species from different parts of the world [ 67 , 68 , 69 , 70 , 71 ]. The debate regarding the vast fungal biodiversity linked to direct the resources for the discovery of new SMs especially from newly identified fungi species which needs further research to characterize those SMs and their mode of action.…”
Section: Fungi Contribution As Antioxidant and Anticancer Productsmentioning
confidence: 99%